The Implication of Different Volumes of Amniotic Fluid in Predicting Neonatal Outcome - Kasi, Najia; Shaista Ambreen; Shazia Awan; Arshad Khushdil; Lubna Noor; Nidda Yaseen; Sehrish Raja (Indus Journal of Bioscience Research, 2025)
Background: Amniotic fluid index (AFI) variations has been associated with adverse perinatal outcomes, including increased cesarean delivery rates and neonatal complications. Accurate monitoring of AFI is essential for predicting and managing high-risk pregnancies effectively. Objective: To evaluate the predictive value of AFI for adverse perinatal outcomes, including neonatal morbidity and delivery mode, in term pregnancies. Study Design: Prospective cohort study. Duration and Place of Study: The study was conducted from June 2023 to December 2023 at the Department of Obstetrics and Gynaecology, CMH Multan. Methodology: A total of 60 term pregnancies were included, divided into two groups: Group A (AFI 5 cm). Patients were aged 18–40 years with singleton, non-anomalous pregnancies at ≥37 weeks gestation. Exclusion criteria included pre-existing medical conditions, multiple pregnancies, and prior cesarean delivery. AFI was measured using the four-quadrant technique, and neonatal outcomes such as Apgar scores, birth weight, NICU admissions, and respiratory distress were assessed. Non-stress test (NST) reactivity and delivery mode were also recorded. Results: Group A exhibited significantly higher rates of cesarean deliveries (66.7% vs. 20%, p